Synoptic-scale variability in the Beaufort High and spring ice opening in the Beaufort Sea - Huang, Yingqi; Bai, Xuezhi; Leng, Hengling (Frontiers in Marine Science, 2022)
This study examines the role of synoptic-scale variability in the Beaufort High in spring ice opening in the Beaufort Sea using data over the 2000-2019 period. A few days before ice opening in spring, the Beaufort High begins to strengthen, deform, and shift eastward from the Chukchi Sea to the western Canadian Arctic Archipelago due to warming in eastern Siberia, and the Aleutian Low is also enhanced. The pressure gradient between the Aleutian Low and the Beaufort High increases rapidly, promoting strong southeasterly winds. As the Beaufort High shifts eastward, the anticyclonic sea ice circulation in the Beaufort Sea tends to be an asymmetrical gyre; as a result, sea ice in the eastern Beaufort Sea is exported toward the western Beaufort Sea without supplementation from the north. Sea ice volume budget analysis indicates that when southeasterly winds are prevailing, wind-forced ice advection and divergence dominate the ice opening in the southeastern Beaufort Sea. Although both the basal and lateral melting are promoted during the ice opening, their contributions to the reduction of ice volume are negligible.